2020
DOI: 10.1096/fasebj.2020.34.s1.02372
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetylation on isocitrate dehydrogenase 1 regulation

Abstract: Isocitrate dehydrogenase 1 (IDH1) is a metabolic enzyme responsible for catalysis of isocitrate to α‐ketoglutarate using NADP+ as a cofactor. Cancerous mutations of IDH1 yield the neomorphic conversion of α‐ketoglutarate to D‐2‐hydroxyglutarate, a proposed oncometabolite. Various cancers such as gliomas, glioblastomas, acute myeloid leukemias, and bone cancers, are driven by IDH1 mutations. Although it has been established that IDH1 is an enzymatic driver of disease, more research is necessary to elucidate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have shown that when a single amino acid change occurs in a conserved arginine residue in the isocitrate-binding site of IDH1, it will lead to a decrease in the enzymatic activity of the oxidative decarboxylation of isocitrate to α-ketoglutarate [ 35 ]. In addition, it has been shown that acetylation may be an important posttranslational modification that regulates the catalytic efficiency of IDH1 and is associated with IDH1 activity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that when a single amino acid change occurs in a conserved arginine residue in the isocitrate-binding site of IDH1, it will lead to a decrease in the enzymatic activity of the oxidative decarboxylation of isocitrate to α-ketoglutarate [ 35 ]. In addition, it has been shown that acetylation may be an important posttranslational modification that regulates the catalytic efficiency of IDH1 and is associated with IDH1 activity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%